PENYU SEBAGAI IDE DALAM SENI KRIYA KERAMIK - BAYU ARI ANGGORO, Dra. Jupriani, M.Sn., Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of creating final work is to visualize the beauty of turtle in ceramik craft art. This craft is in form of three dimensional object. The writer makes unique shape and character of turtle as inspiration of creating this work, by using some basic techniques in forming ceramic. Process of forming uses technique of pinching, slab, turning and technique coil. The writer gives colors and motifs so that it looks more attractive and has artistic value. Total of work that is made by writer is eight works with title, belanga, tempat lilin, asbak, piring, guci, vas bunga, pajangan dinding, wadah buah.Keywords: Sea Turtles and Ceramic Craft Artl